OVERCOMING THE INFLUENCE OF SOCIAL MEDIA BASED ON STUDENTS’ GENDER DIFFERENCES - Maranita, Rani; Avicienna, Razes Maskawaih; Muawanah, Risalatul; Mursydan, Zaka Kharis (Universitas Negeri Malang, 2019)
This study investigates the causal relationships between social media (Instagram) use of college students based on gender differences. We conducted a panel survey targeting State University of Malang college students and analyzed 50 responses which proportion is 50% males and 50% females to get balanced and maximum results. The following results were produced: (a) The college students in the study reported that students use social media as entertainment, friendship, and as well as a place to find news they like and need. Instagram is also used as a media for exchanging information that is assured by them; (b) for male students, instagram is used as a media to find their favorite news such as sports news and games, and this has no effect on their social life.; and (c) for female students, instagram is a part of their lives.